Polygala arvensis Willd.: A taxonomic note for the Flora of Nepal (Botanica Orientalis: Journal of Plant Science, 2025)
This paper reports Polygala arvensis Willd. from the Siwalik region of central Nepal as a new addition to the flora of Nepal. Detailed information about this species, including description and taxonomic treatment, is provided.